Konten Visual dan E-WOM Instagram terhadap Keputusan Pemilihan Puri sebagai Destinasi Prewedding - Ni Made Ayu Natih Widhiarini; I Nyoman Sudiarta; Ni Putu Feby Devira Permanita (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of digital technology has significantly transformed the tourism industry, including the emergence of the prewedding tourism trend. This study aims to analyze the impact of visual content and Electronic Word of Mouth (E-WOM) on Instagram on tourists' decisions in choosing Puri as a prewedding destination. Using a quantitative approach with Structural Equation Modeling (SEM) analysis, the study involved 100 respondents selected purposively. The focus of this study was on four Puris with strong Instagram presence, namely Puri Rangki, Puri Saren Kawan Tabanan, Puri Lanang Sibang Kaja, and Puri Tresna Villas. The results show that both visual content and E-WOM have a significant impact on the visit decision, with visual content having a more dominant effect. These findings indicate that attractive visual marketing strategies and effective use of E-WOM are key factors in influencing potential visitors' decisions regarding prewedding tourism destinations. This study contributes to the development of tourism marketing strategies, especially in utilizing Instagram as an effective promotional tool to attract tourists' attention.